2021
DOI: 10.1097/inf.0000000000003264
|View full text |Cite
|
Sign up to set email alerts
|

Effective Treatment of Chronic Hepatitis C Virus Infection With Ledipasvir/Sofosbuvir in 2 Teenagers With HIV Coinfection: A Brief Report

Abstract: The therapeutic program was carried out thanks to the donation of LDV/SOF provided by the producer (Gilead Sciences Poland Sp. z o.o.). The pharmaceutical company did not have any role in performing the study, nor in writing or approving this article. M.P.Ś. performed the research, designed the research study, collected and analyzed the data, contributed to the interpretation of the data and drafted the article; A.D. and A.O. collected and analyzed the data; M.M. contributed to the study design and critically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…This observation was similar to our results: our per-protocol SVR12 rates were 100% irrespective of the HCV genotype, duration of the treatment, previous treatment experience, or baseline extent of liver fibrosis (Table 2). It is worth emphasizing that the treatment was effective in cirrhotic patients and in two participants coinfected with HIV, as described in detail in another paper [25]. In addition, one of our patients had evidence of past HBV infection with detectable anti-HBc total antibodies.…”
Section: Discussionsupporting
confidence: 52%
“…This observation was similar to our results: our per-protocol SVR12 rates were 100% irrespective of the HCV genotype, duration of the treatment, previous treatment experience, or baseline extent of liver fibrosis (Table 2). It is worth emphasizing that the treatment was effective in cirrhotic patients and in two participants coinfected with HIV, as described in detail in another paper [25]. In addition, one of our patients had evidence of past HBV infection with detectable anti-HBc total antibodies.…”
Section: Discussionsupporting
confidence: 52%
“…Although DAAs have been approved for treatment of adolescents since 2017, DAA use for treatment of HIV/HCV coinfected children and adolescents in real-world settings has only been reported for 2 adolescents from Poland. 11 In this study, we report outcomes of 6 adolescents living with HIV and chronic HCV in the Ukraine Paediatric HIV Cohort Study who have received DAAs to date. Similar to the results from Poland, 11 our analysis showed that DAA-based treatment was well tolerated and all patients achieved SVR12 within routine clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…11 In this study, we report outcomes of 6 adolescents living with HIV and chronic HCV in the Ukraine Paediatric HIV Cohort Study who have received DAAs to date. Similar to the results from Poland, 11 our analysis showed that DAA-based treatment was well tolerated and all patients achieved SVR12 within routine clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Among HIV/HCV-coinfected adults, HCV treatment is highly efficacious with curative rates comparable to those with HCV monoinfection [50,51]. Thus far, at least 11 cases of successful DAA treatment have been reported in coinfected children [15 ▪▪ ,16,52 ▪ ,53].…”
Section: Direct-acting Antiviral Regimens In Real-world Settings and ...mentioning
confidence: 99%